Rapid determination of hexapeptides by hydrophilic interaction LC–MS/MS for in vitro skin-penetration studies. (June 2013) - Zhou, Wanlong; Wang, Perry G; Ogunsola, Oluwatosin A; Kraeling, Margaret EK
Background: A sensitive analytical method is needed for assessing penetration of topically applied peptides for in vitro skin-penetration studies.Results: A rapid hydrophilic interaction LC (HILIC)–MS/MS method for analyzing the polar peptides Ac-EEMQRR-amide and H2 N-EEMQRR-amide in various skin layers and matrices has been developed and evaluated. The matrices included emulsion, receptor fluids, cotton-tipped applicators, stratum corneum tape strips, epidermis and dermis of the skin. Stable isotopically labeled analogues were used as internal standards to correct for recovery and matrix effects. A HILIC-SPE procedure was optimized to minimize significant ion suppression in the more complex matrices.Conclusion: This HILIC–MS/MS method is applicable to the determination of Ac-EEMQRR-amide and H2 N-EEMQRR-amide in complex skin samples and other matrices generated during in vitro skin-penetration studies.